Study of the Genotoxic Effect of Polluted Water of Certain Ponds of Narsinghpur in the R B Cs of the Fish Catla catla by Applying Micronucleus Assay - Vineeta Girdoniya, Dr (International Journal of Pharmaceutical & Biological Archive, 2016)
Study of the Genotoxic Effect of Polluted Water of Certain Ponds of Narsinghpur in the R B Cs of the Fish Catla catla by Applying Micronucleus Assay